Teaching English Through Voter Education: A Curriculum Integration Model for Sri Lanka Secondary Schools - Vivekanantharasa, Raveenthiran; Kurniati, Erisa (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2025)
Study This aim develop an integration model effective curriculum​ For teach education voters through English learning in schools​ Sri Lankan middle school . With use Design and Development Research (DDR) approach , research done through three stage systematic : (1) analysis need through studies document curriculum national and interview with five English teachers , (2) designing the “CLIL-Based Voter Education Framework” model, and (3) validation of the model by experts and discussion group with teachers. Research results show that teachers support integration education voters to in English learning , but​ need structured guides , contextual teaching materials , and easy pedagogical strategies​​ adapted . Resulting model assessed feasible , practical , and relevant by experts and teachers, with component main in the form of module thematic , glossary term political in English , and guide implementation based CLIL principles . Research This conclude that this model can become solution operational for teachers in integrate education democracy to in English curriculum , as well as support vision reform Sri Lanka education 2022-2032 which focuses on the formation of competent and responsible citizens​ answer . Recommendation given for trial​ more area and development training companion for teachers.